Enjoyment and Not Competence Predicts Academic Persistence for Distance Education Students - Brubacher, Michael R; Silinda, Fortunate T (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
Dropout rates of distance education students is a serious problem for many distance education institutions as well as their students. A psychological factor that is related to dropout is the academic persistence of students, or their intent to finish their degrees. One factor that could predict academic persistence, which is often used to identify and help at-risk students, is the academic competencies of students. However, another factor that could predict persistence is the intrinsic motivation of students, or whether they enjoy their academic work and find it interesting. In the present study, 350 distance education undergraduates in South Africa completed a survey that measured their persistence, perceived academic competence, and intrinsic motivation. The survey also measured experienced workload, help-seeking attitudes, and general stress. Results show that intrinsic motivation was a significant predictor of persistence while competence was not. Further, help-seeking attitudes and general stress had indirect effects on persistence through intrinsic motivation. The study highlights the need for educators to be aware of the intrinsic motivation of distance education students, and the factors that could impact it, in order to increase the academic persistence of students.